1993
DOI: 10.1111/j.1468-3083.1993.tb00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Sweet's syndrome associated with ovarian carcinoma

Abstract: Sweet's syndrome is sometimes associated with haematological malignancies and less frequently with solid tumors. We report a new case of association of a Sweet's syndrome with an ovarian carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…To our knowledge, there have been 4 cases reported of Sweet’s Syndrome in the context of ovarian carcinoma prior to this case report: two likely as a sign of cancer recurrence ( Nguyen et al, 1983 Aug , Ehrsam et al, 2006 ), one with Sweet’s Syndrome as a presenting feature that led to work up revealing cancer ( Fader et al, 2012 ), and one temporally related to medication administration of topotecan chemotherapy ( Dickson et al, 2013 Jan ), Sweet’s Syndrome has also been reported in the context of non-ovarian gynecologic malignancies; the majority of cases have been identified in the setting of cervical cancer ( Clark et al, 2017 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, there have been 4 cases reported of Sweet’s Syndrome in the context of ovarian carcinoma prior to this case report: two likely as a sign of cancer recurrence ( Nguyen et al, 1983 Aug , Ehrsam et al, 2006 ), one with Sweet’s Syndrome as a presenting feature that led to work up revealing cancer ( Fader et al, 2012 ), and one temporally related to medication administration of topotecan chemotherapy ( Dickson et al, 2013 Jan ), Sweet’s Syndrome has also been reported in the context of non-ovarian gynecologic malignancies; the majority of cases have been identified in the setting of cervical cancer ( Clark et al, 2017 ).…”
Section: Discussionmentioning
confidence: 90%
“…Approximately 21% of Sweet’s Syndrome cases observed appear to be associated with hematologic or solid tumor malignancies ( Cohen et al, 1988 ). The list of conditions and malignancies associated with SS continues to grow, but, reports associating Sweet’s Syndrome with gynecologic malignancies are sparse in the literature ( Fader et al, 2012 , Culp et al, 2004 , Nguyen et al, 1983 Aug , Ehrsam et al, 2006 , Clark et al, 2017 ). There is a particular paucity of reports involving malignancy of ovarian origin with only four cases reported.…”
Section: Introductionmentioning
confidence: 99%